Children's Human Rights Education as a means to Social Justice: A Case Study from England - Katherine Covell (Universidad Autónoma de Madrid, 2013)
Social justice depends in part on the existence and knowledge of human rights instruments. It depends also on the motivation for action to promote and protect the rights of all persons. This requires effective human rights education. Although many human rights instruments have been agreed upon, effective human rights education, defined as that which provides the skills and motivation to ensure rights are respected, has been lacking. Rather than the widespread and systematic inclusion of human rights education in schools as called for by UN bodies, for the most part human rights education has been left to efforts by non-governmental organizations. This article, a case study of children's human rights education in England, describes an exception. In Hampshire County Education Authority, schools were re-structured to use the rights described in the UN Convention on the Rights of the Child as the overarching framework of all their teaching and functioning. The findings of separate studies over an eight year period that assessed the outcomes of the rights-based schools are summarized here. Over time, children become increasingly respectful of the rights of others, showing positive attitudinal and behavioral changes. The findings over time strongly suggest that schools in which the rights of the child are both explicitly taught and practiced are an effective means of promoting social justice.